Circumplex Scales of Intergroup Goals: An Interpersonal Circle Model of Goals for Interactions Between Groups. (April 2014) - Locke, Kenneth D.
Six studies ( N = 1, 682) used the Circumplex Scales of Intergroup Goals (CSIG)—an inventory based on the interpersonal circle—to assess individuals' agentic and communal goals for interactions between groups (nations in Studies 1-4, organizations in Study 5, political parties in Study 6). Noteworthy findings included the following: People with stronger unagentic-and-uncommunal goals perceived other groups as dangers, were wary of intergroup negotiations, and sanctioned authoritarianism and inequality. People with stronger agentic-and-uncommunal goals proudly identified with their country and compatriots, disapproved of nations unlike their own, and preferred the conservative candidate in a national election. People with stronger communal-and-unagentic goals identified with people beyond their ingroup, and wanted their group to resolve intergroup conflicts by behaving cooperatively rather than competitively or aggressively. By providing an encompassing framework capable of organizing and integrating these types of diverse findings, the circumplex model can facilitate cumulative scientific progress.